EQUIVOCO HISPANIMO: NOTAS SOBRE EL EXILIO REPUBLICANO Y PENSAMIENTO REACCIONARIO EN EL MEXICO DE LOS AÑOS 1940 - Krauel, Javier (Res Publica. Revista de Historia de las Ideas Políticas, 2009)
This essay sustains an essential similarity between liberal Hispanism, as developed by post-Civil War exiles, and the theory of hispanidad elaborated by conservatives such as Maeztu, premised on the imperial presuppositions that seem to determine every relationship between Spain and Latin America.